Assistance in the Al-Miftakh Method as an Effort to Improve Religious Text Reading Skills at Garanggung Islamic Boarding School Karawang Regency - Undang Ruslan Wahyudin; Hinggil Permana; Ella Nurlailasari; Ridwan Irwansyah (Universitas Nurul Jadid, 2024)
This community service program focuses on the implementation and impact of the Al-Miftakh method in enhancing the ability to read religious texts at Garunggung Islamic Boarding School in Karawang Regency. The Al-Miftakh method is a structured approach aimed at improving the reading proficiency of religious texts by providing a systematic and practical framework for learning. The program seeks to enhance the santris' skills in reading classical Islamic texts, enabling them to gain a deeper understanding of both content and context. The community service involved a series of workshops and hands-on training sessions where santri were systematically guided through the Al-Miftakh method. The sessions were followed by assessments to evaluate their progress. The results indicated that the Al-Miftakh method significantly improved reading fluency and comprehension among the participants. Out of 85 students involved in the program, 89% reported an improvement in their skills based on post-training surveys. This program concludes that structured reading methods like the Al-Miftakh method are highly effective in contributing to the educational development of santri in Islamic boarding schools, offering them valuable tools to better understand religious texts.